Adsorption Capacity and Phosphate Removal Efficiency of Oyster Shells and its Implications to Chemistry Learning - John Rommel T. Retuya; Victoria N. Malaya (Gagasan Pendidikan Indonesia, 2023)
The aquaculture sector of the Philippines which includes fish pond culture systems faces many challenges and issues such as high concentration of phosphate which does not only affect water parameters but also triggers the occurrence of Harmful Algal Blooms. Hence, this study was conducted to evaluate the adsorption capacity and phosphate removal efficiency of oyster shell powder (OSP) using brackishwater under laboratory conditions as learning resources of chemistry learning. This quantitative research study used Completely Randomized Design (CRD) with three treatments: T1 (Control/Commercial) – 1.5g Calcium carbonate (CaCO3); T2 – 1.5g Oyster Shell Powder (OSP); T3 – 2.5g Oyster Shell Powder (OSP). Results revealed that in terms of surface morphology, the photographs showed irregularity of shapes and different sizes, implying heterogeneity of OSP while, in terms of elemental composition, Calcium and Oxygen are the major elemental composition of the OSP. Further, in terms of Phosphate Adsorption Capacity, One Way ANOVA revealed significant differences (p-value <0.01) among treatments. Further analysis using LSD revealed that commercial calcium carbonate has significantly higher adsorption capacity than oyster shell powder, however, 1.5 g OSP has higher adsorption capacity than 2.5g OSP. Furthermore, in terms of phosphate removal efficiency, One Way ANOVA revealed no significant differences (p-value <0.05). This means that the phosphate removal efficiency of OSP is comparable to commercial calcium carbonate (CaCO3).Moreover, the study's findings act as an educational resource, facilitating a profound comprehension of the practical applications of chemistry principles. It encourages chemistry learners to engage in critical evaluation and practical application of their knowledge, particularly in addressing pressing environmental challenges.